Sosialisasi Pelatihan UMKM Untuk Membangun Bisnis Yang Berkelanjutan Dan Menjanjikan - Bahtiar, Yuyun; Nisak Nur, Luluk Choirun; Afidah, Nurul; Agustina, Ulfa Wulan; Ma'Arif, Iin Baroroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Entrepreneurship is one of the important factors in strengthening the Indonesian economy, especially through the Micro, Small and Medium Enterprises (MSMEs) sector which has proven to be resilient in facing the global crisis. Kepuhrejo Village, Jombang Regency, has abundant natural potential, such as tamarind and spices, but has not been optimally utilized. Through a community service program, students carry out training to maximize this natural potential in order to develop traditional herbal medicine-based products that can improve the local economy. This activity aims to build community interest in entrepreneurship, provide innovation in the utilization of local resources, and create sustainable business opportunities. The method used is Community Based Research (CBR), involving local communities in training in making herbal medicine products from natural ingredients. The results of the activity show an increase in community awareness of the potential of the surrounding nature and the ability to create products of high economic value. This program has succeeded in contributing to the development of MSMEs in kepuhrejo Village, as well as opening up wider and more sustainable business opportunities for the local community.